Sexual Differences in Physiological and Transcriptional Responses to Salinity Stress of Salix linearistipularis - Feng, Shuang; Sun, Hongwei; Ma, Hongping; Zhang, Xin; Ma, Shurong; Qiao, Kun; Zhou, Aimin; Bu, Yuanyuan; Liu, Shenkui (Frontiers in Plant Science, 2020)
Willow (Salix), a dioecious plant, is an important ornamental tree species in the world. Salix linearistipularis, a perennial woody plant species naturally distributed on the Songnen Plain saline-alkali land in northeast China, has a higt to saline conditions. To study the sexual differences of S. linearistipularis in salinity tolerance, the physiological and transcriptional responses to salinity were compared between female and male cuttings. Under salinity stress, the female leaves exhibited higher superoxide dismutase and peroxidase activities and photosynthetic capacity, and lower H2O2 contents than those of male leaves. Under salinity stress, sodium (Na+) accumulation in female leaves was lower than that in the male leaves. The non-invasive micro-test showed that the net Na+ efflux in the salt-treated female roots was higher than that in male roots. Physiological responses revealed that female cuttings were more tolerant than males, which may be mainly due to females having lower leaf Na+ accumulation and higher root Na+ efflux capacity than males. Transcriptional analyses showed that 108 differentially expressed salt-responsive genes were identified in both female and male roots; most of these showed sexual differences in expression patterns under salinity stress. RNA-seq combined with qPCR analysis showed that the salt-induced expression of four Na+/H+ antiporter (NHX) genes (SlNHX3, 5, 6, 7) in female roots was higher than that in male roots. Transcriptional analyses revealed that the higher Na+ efflux capacity in female roots than in male roots may be closely related to the differential expression of salt-responsive genes, especially NHX genes.